Cyber‐harassment victimization of Portuguese adolescents: A lifestyle‐routine activities theory approach. (14th September 2022) - Vale, Maria; Pereira, Filipa; Spitzberg, Brian H.; Matos, Marlene
Abstract: Cyber‐harassment refers to a pattern of repeated, intentional, and unwanted annoyances, impositions, threats, or other aggravating actions mediated by Information and Communication Technologies. Globally, substantial proportions of adolescents experience cyber‐harassment, resulting in a host of deleterious health‐related consequences. This study tested the empirical utility of the Lifestyle‐Routine Activities Theory in accounting for adolescent cyber‐victimization. A representative sample of 627 adolescents, aged 12–16, enrolled in schools from northern Portugal and Azores, were surveyed. Consistent with the theoretical assumptions, older adolescents, who used tablets, published information on social network profiles, added unknown people as friends, met face‐to‐face with them, and had parents with less knowledge of their online contacts were at increased risk of being cyber‐victimized. Theoretical and practical implications are elaborated.